Cadeau: Smart Gifting Platform - Noor Sayeh; Ro’a Abu Libdeh (My University, 2025)
In today’s digital economy, the demand for personalized and emotionally engaging e commerce experiences has never been higher. Cadeau is a next-generation online gift shopping platform that bridges the gap between traditional gifting and modern, intelligent user experiences. The platform aims to revolutionize the way people select, customize, and purchase gifts by providing a dynamic, interactive, and AI-powered environment that caters to the emotional and practical needs of customers. At the heart of Cadeau lies a personalized virtual assistant that interacts with users, offers tailored recommendations, and guides them through smart search experiences based on preferences and occasions. This avatar transforms the user journey from a simple trans action into a meaningful, guided experience. In addition, Cadeau supports full product customization with real-time 3D previews, allowing users to visualize changes before com mitting to a purchase. Customers are empowered to create truly unique and expressive gifts. For those who enjoy spontaneity, the platform also includes a gamified ”surprise shopping mode,” where users can receive mystery boxes or randomized gifts that align with their stated preferences—adding a fun, interactive twist to traditional shopping. The expe rience is further enhanced by a point-based rewards system that encourages continued engagement and loyalty. Beyond the customer experience, Cadeau offers robust features for business users and administrators. Business owners can manage inventory, upload products, respond to orders, and engage with customers via a dedicated dashboard. Meanwhile, the admin panel includes tools for overseeing platform users, managing content, and ensuring system wide efficiency. Built using modern technologies such as Flutter, Node.js, MongoDB, and integrated AI systems, Cadeau is not just a gift shop—it’s a comprehensive digital ecosystem designed to elevate the act of gifting. By combining intuitive design, emotional intelligence, and personalization, the Cadeau project delivers a uniquely powerful and heart-centered ap proach to e-commerce in the 21st century.